The Emerald international handbook of technology-facilitated violence and abuse - Bailey, Jane; Flynn, Asher; Henry, Nicola (Emerald handbooks, 2021)
Digital technologies have led to many important social and cultural changes worldwide, but they are also implicated in the facilitation of violence and abuse. While cybercriminality is often described as one of the greatest threats to nation states and global security, the wide range of interpersonal crimes comprising technology-facilitated violence and abuse (TFVA) -- including, but not limited to, image-based sexual abuse, hate speech, online sexual harassment, and cyberstalking -- has received comparatively less attention. This handbook features theoretical, empirical, policy, and legal analysis of TFVA from over 50 multidisciplinary scholars, practitioners, advocates, survivors, and technologists from 13 countries. Addressing a spectrum of abuse perpetrated online, offline, and through new technologies, the book sets TFVA in the context of intersecting underlying systemic drivers -- including misogyny, racism, classism, colonialism, ableism, ageism, transphobia, and homophobia -- and discusses ways forward in effectively responding to TFVA. Adopting a holistic approach, it explores a host of issues relating to TFVA, including the nature and experience of harmful and criminal conduct; organizational responses; regulatory, legal, and ethical concerns; corporate and social responsibility; justice for victims; bystander intervention; and cultural and social attitudes. The handbook's international, interdisciplinary, and intersectoral nature affords opportunities for learning from common experiences, but it also emphasizes the equality-affirming importance of avoiding one-size-fits-all analyses that fail to reflect rich and diverse experiences from around the world--back cover